Inequality undermines democracy and growth - Gylfason, Thorvaldur (Munich, 2018)
"Income equality and trust seem to go along with several other ingredients of social capital as determinants of economic growth across the globe. In a large sample of countries, equality in the distribution of income as measured by the World Bank and by The Standardized World Income Inequality Database are seen to be correlated with economic diversification, the rule of law, transparency as measured by the corruption perceptions index from Transparency International, trust as measured in the World Values Survey, and democracy, all of which are good for growth as reflected in the purchasing power of per capita national income."